2022
DOI: 10.1017/s0967199422000405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cis-9, trans-11 and trans-10, cis-12 conjugated linoleic acid supplementation on maternal reproductive parameters

Abstract: Summary Conjugated linoleic acid (CLA) is a mixture of positional isomers of linoleic acid found in ruminant products and meat. The diet supplementing with CLA is an emerging area, requiring studies to elucidate its effects on animals and human reproduction, as well as its side effects. Therefore, the aim of this study was to evaluate the effects of CLA gastric administration, during the pregestational and gestational period in biometric and reproductive parameters, as well as in ovarian morphophysiology. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 45 publications
9
4
1
Order By: Relevance
“…Abazarikia et al [43] state that the inclusion of CLA in oocyte maturation and in vitro embryo culture can affect the modulation of lipogenesis. The data in the current study corroborate those of Freitas et al [11], as supplementation of the maternal diet CLA, did not alter the lipid content of oocytes included in antral follicles.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Abazarikia et al [43] state that the inclusion of CLA in oocyte maturation and in vitro embryo culture can affect the modulation of lipogenesis. The data in the current study corroborate those of Freitas et al [11], as supplementation of the maternal diet CLA, did not alter the lipid content of oocytes included in antral follicles.…”
Section: Discussionsupporting
confidence: 92%
“…The current study demonstrated that animals born to mothers supplemented with CLA did not show alterations in body weight and the obesity index, as previously reported for parental [11] and corroborating the literature [23]. Some studies evaluated weight gain in CLA-treated animals and reported similar findings.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations